The (de-)radical(-ising) potential of r/IncelExit and r/ExRedPill. (June 2023) - Thorburn, Joshua
This article introduces two forums, r/IncelExit and r/ExRedPill, that have organically emerged in recent years to provide a pathway out of the manosphere for men and boys. Based upon preliminary findings from a broader digital ethnography project, this piece highlights the potential benefits these spaces can offer individuals engaging with them. Furthermore, this article flags opportunities that exploring these forums can offer to academic inquiry on the nature of (de-)radicalisation within the manosphere, along with theoretical issues debated within the critical studies of men and masculinities field. It is also proposed that such forums could serve as an alternative space to provide socially alienated young men and boys with information emphasising the importance of consent and respectful relationships, away from formal school curricula. Finally, this article also discusses the potential effects that neoliberalism may have in shaping how young men approach dating.